SCIENTIFIC AND THEORETICAL BASES OF NATURAL SCIENCES IN THE DEVELOPMENT OF AESTHETIC EDUCATION OF PRIMARY SCHOOL STUDENTS (ResearchJet Journal of Analysis and Inventions, 2021)
The problem of nature-society-human relations is of great importance today. Society, man's activity towards nature is becoming more and more tense. For this reason, the spiritual and social approaches of mankind to nature are being studied and analyzed.